Efek Antiplasmodium Ekstrak n-Heksana Kulit Batang Mundu (Garcinia dulcis Kurz.) Dengan Parameter Jumlah Leukosit Dan Hemoglobin Pada Mencit Swiss Webster Yang Diinfeksi Plasmodium Berghei - Ruly Anggrayni; Gunawan Pamudji Widodo; Dwi Ningsih (Jurnal Farmasi Indonesia, 2011)
Malaria is a parasitic disease caused by protozoa of plasmodium genus. Mundu (Garcinia dulcis Kurz.) is one of the potential with the chemical compound xanton and triterpenoid for antiplasmodial. The aim of this experiment was to find out the effect of mundu (Garcinia dulcis Kurz) cortex n-hexane extract on leucocytes amount and hemoglobin level in mouse infected with Plasmodium berghei, and to know the dose of the most effective n-hexane extract as antiplasmodium. Mundu extract made by maceration use n-hexane. The animal test mice before treatment with extract induced by Plasmodium berghei to the number of erythrocytic in the blood of 107 and the concentrate extract was tested in each group of animals test with a dose of 50 mg / kg bw mice, 100 mg / kg bw mice and 150 mg / kg bw mice, negative control group were given 0.5% CMC and the positive control were given chloroquine be suspention in CMC solution. The anti-plasmodium effect was observed by calculating the leucocytes amount and hemoglobin level. Data was prosessed with one way ANOVA statistical test followed by tukey test. The result of the experiment showed that n-hexane extract of mundu cortex had the anti-plasmodium effect by decrease the leucocytes amount and increase hemoglobin on the mouse induced with Plasmodium berghei. The most effective dose of mundu cortex n-hexane extract was 100 mg/kg BW.